A study of the effects of power matching techniques on the performance of RF CMOS low-noise amplifers - Gusad, Maria Theresa Abalos (2004)
In this thesis, the effects of different power matching techniques on the performance of CMOS LNAs are investigated. A methodology adapted from discrete component RF circuit design is employed in designing the matching networks of the circuit. Using a 0.25 nm CMOS process, 22 LNA circuits employing the common-source topology with cascode configuration are implemented and fabricated. These circuits differ with each other in terms of various device and design parameters. The effects of these parameters on the LNA's performance are characterized. It is established that with proper choice of device and design parameters, better LNA performance could be achieved. Simulation and measurement results are also compared and analyzed; thus demonstrating the need to modify the BSIM3v3 transistor model to include the effects of the gate resistance and the substrate network on the behavior of the LNA at RF.